Modality in Text: a Proposal for Corpus Annotation - Hendrickx, Iris (2012)
We present a annotation scheme for modality in Portuguese. In our annotation scheme we have tried to combine a more theoretica llinguistic view point with a practical annotation scheme that will also be useful for NLP research but is not geared towards one specificapplication. Our notion of modality focuses on the attitude and opinion of the speaker or of the subject of the sentence. We validated the annotation scheme on a corpus sample of approximately 2000 sentences that we fully annotated with modal information using the MMAX2 annotation tool to produce XML annotation. We discuss our main findings and pay attention to the difficult cases that we encountered as they illustrate the complexity of modality and its interactions with other elements in the text.